Error Modelling of a Silicon Angular Rate Sensor - Marselli, C.; Amann, Hans Peter; Pellandini, Fausto; Grétillat, F.; Grétillat, M.-A.; de Rooij, Nicolaas F. (My University, 1997)
The coupling between microsensors and efficient signal processing is essential to achieve demanding specifications for navigation applications. The performances of a silicon micromachined angular rate sensor are outlined showing that the main shortcoming consists of an important offset drift. This error is modelled and used in a correction algorithm based on Kalman filtering. The filter aims at estimating the sensor errors, like the offset, and the real angular rate, measuring the output voltage. Tests show that the accuracy is greatly improved.